The Implication of Local Wisdom-Based Geographical Curriculum and its Course Book on the Cosmocentric Attitude of the Students in Bali Upland Region - Ida Bagus Made Astawa (Jurnal Pendidikan dan Pengajaran, 2022)
The ability of teachers in Bali to write lesson plans that contain local wisdom is also low, while the competence of local wisdom is high. It happens because the teacher does not yet have a guideline to be used as a reference in compiling the syllabus and lesson plans. This study aims to analyze the implications of applying the geography curriculum based on local wisdom and its textbooks to the cosmocentric attitude of high school students in the highlands of Bali. This study was designed as a "causal-comparative study" with purposively determined samples in two public high schools in the highlands of Bali. Data from teaching were collected using observation sheets and data about students' cosmocentric attitudes using a questionnaire (Likert model). Data were analyzed quantitatively using a t-test at a significance level of 1%. The results showed that the scores of students' concentric attitudes in the highlands of Bali increased after implementing the Geography curriculum based on local wisdom and textbooks as a complement to teaching Geography. The increase occurred consistently in all classes (Class X, XI, and XII), with an average score of 25.58% increase. The results of statistical tests show a significant difference in cosmocentric attitudes before and after implementing the geography curriculum based on local wisdom with textbooks as a complement to teaching. It shows that the supplement to the local-based geography curriculum and textbooks has positive implications for the cosmocentric attitude of students in senior high schools in the highlands of Bali.